Hormones demands of judo training test - Henriques-Neto, D.; Carratala, V.; Fernandes, L.; Pablos, C.; Garcia, J. M. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
Using a biochemical analysis in saliva, to identify the response of testosterone (T) and cortisol (C) on the application of a specific test for Judo. For this we used a sample of 9 judoka, male, 24.1 ± 3.1 years of age, 180 ± 8.4 cm in height and 73.3 ± 8.3 Kg in weight that participated in this study. It examined the concentration hormonal (cortisol and testosterone) me four times, M1 (rest 24 hours before the test); M2 (pre-test); M3 (post-test) y M4 (24 hours after the test). Were produced significant increases in M1 M2 and M3. A significance level of p<0.05 was applied. In relation to the concentration of testosterone, there is a significant increase in the following moments of evaluation: M1-M3 (p=0.001); M2-M3 (p=0.001) and a significant decrease in M3-M4 (p=0.005). The level of concentration of cortisol presents an increase at the same moments M1-M3 (p=0.015); M2-M3 (p=0.047) and a decrease in M3-M4 (p=0.004). It can be concluded that the specific Test, stimulates a great hormonal response to the level of cortisol levels of testosterone. The test can be characterized as an activity short and intense, and yet a good meter of the state of force resistant specifies in Judo.